Immediate effect of pre-made foot orthotics on variability and joint coupling patterns of rear foot and tibia during gait in male athletes with pes planus - Heydar Sadeghi; Peyman Aghaie Ataabadi; Fariborz Hovanlo (Biyumikānīk-i varzishī, 2015)
Objective: The purpose of this study was to investigate the immediate effects of pre-made foot orthotics on rear-foot and tibia variability and joint coupling patterns during stance phase of gait in male athletes with pes planus.